Cellular and Biochemical Studies on Risperidone Induced Teratogenesis in Developing Chick Embryos - Dr. Pinakin Wagh; Saurabh Dey; Nistha Ananda; Navinya Gawali; Hritika Shinde (International Journal of Pharma and Bio Sciences, 2022)
Risperidone is a second-generation antipsychotic drug that exhibits D2, 5-HT2A, α1, α2, and H1 receptor affinity. Patients suffering from Schizophrenia are prescribed with this drug. It is mostly used for controlling the overactivity of the central mesolimbic and mesocortical pathways of the patients. According to the studies conducted it has been found that Risperidone possesses teratogenic actions on various model organisms. Consumption of this antipsychotic drug is not only associated with behavioural changes but also with physical alterations. It increases the risk by elevating nitric oxide levels and activating macrophages which leads to apoptotic events in the viable cells. Furthermore, it has been established that Risperidone toxicity caused due to overdose induces neurological as well as cardiovascular defects. Risperidone has the ability to cross the placental barrier and reach the foetal bloodstream intuitively. In addition, Risperidone also gets distributed in the milk of a lactating mother leading to undesirable changes in the breastfed babies. Here in this study, we have shown that Gallus gallus domesticus embryos (HH 23-26) treated with a minimum dose of Risperidone (1000 ppm) altered the protein and enzyme biochemistry with respect to total protein content, alkaline phosphatase (ALP), and Acetylcholinesterase levels. Cell viability studies conducted using flowcytometry have indicated its possible role in the induction of apoptosis as well as necrosis in a developing chick embryo. The present study provides insight into the effects of Risperidone that it may possess on gestating and lactating women. The study also explains the teratogenic potential of Risperidone on target and non-target organisms.